How Prevalent is “Food Addiction”? - Meule, Adrian (Frontiers in Psychiatry, 2011)
Increasing evidence suggests that binge eating-related disorders could be related to addiction-like eating patterns due to the addictive potential of hyperpalatable foods. Subsequently, important implications have been derived for treatment of those disorders and even political actions. However, studies on the prevalence of food addiction are rare. Few recent studies investigated addictive eating in children, adolescents, and adults. This mini-review presents these first attempts to assess addictive eating and how prevalent addictive eating patterns were in the respective studies. It is concluded that the prevalence of food addiction is increased in obese individuals and even more so in obese patients with binge eating disorder. However, prevalence of food addiction is not sufficient to account for the obesity epidemic. Conversely, an arguably high prevalence of food addiction can also be found in under-, normal-, and overweight individuals. Future studies may investigate which factors are associated with addictive eating in non-obese individuals.